Análisis del clima organizacional y motivacional del colegio Policarpa Salavarrieta de Cúcuta (2020)
This research studies the organizational and motivational climate at the Policarpa Salavarrieta school in Cúcuta, to detect the perception that internal clients have of their work environment, evaluating the motivation and the organizational climate in which they operate. The methodology developed is quantitative. The Instrument for the Measurement of School Climate in Institutions of Basic and Middle Education was applied. It was concluded that the operative and administrative personnel are qualified and carry out their tasks fully, which as an organization providing educational services, always seeks to improve offering an excellent quality of service to its different types of clients. The docenes and administrative personnel consider that the work environment is adequate, although there are some disagreements, they like the work they do, the organization that exists within the educational institution, in terms of external factors is a matter of adaptation.